Pengelompokkan Wilayah Bencana Endemi Demam Berdarah Dengue di Jawa Timur dengan Fuzzy Geographically Weighted Clustering - Particle Swarm Optimization - Fikri Handoko Putra; Robert Kurniawan (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2016)
DHF is a disease that is a public health problem and is endemic in almost all districts / cities in East Java. The disease is transmitted through the bite of Aedes aegypti and Albopictus. There is currently no anti-viral drugs and vaccines to prevent dengue fever, then to break the chain of transmission, vector control is considered most appropriate at this time, but because the vector is widespread, it is necessary to control the success of the total coverage (covering the whole area) so that mosquitoes can not be multiply. This research was proposed to investigate of classify the endemic regions in East Java based factor that causes dengue vector control can be focused on certain areas that have the highest potential of dengue fever in East Java. This research was used a method FGWC-PSO to classify areas in East Java with the approach of some of the factors associated with an increase in dengue disease. The data will be used is from the publication of the East Java in Figures In 2013, East Java Provincial Health Profile in 2012, and Indonesian Disaster Data and Information in East Java in 2012. Overall, causes the highest number of dengue fever in some areas in East Java province, namely: